2018
DOI: 10.1002/rcm.8060
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo metabolite identification of a novel benzimidazole compound ZLN005 by liquid chromatography/tandem mass spectrometry

Abstract: Using both in vitro and in vivo methods, we elucidated the metabolic pathway of ZLN005. Phase I metabolites with hydroxylation and carboxylation, as well as phase II metabolites with glucuronide, sulfate and glutathione conjugation, were identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Furthermore, early treatment with lasmiditan for 7 consecutive days from day 1 after surgery delayed the onset of mechanical allodynia in SNI rats. A study has indicated that the half-life of ZLN005 is 11.46 ± 0.67 min in rats ( Sun et al, 2018 ). A clinical study indicated that plasma concentrations of lasmiditan peaked at 1.5–2 h post dose, with a terminal half-life of approximately 4 h ( Tsai et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, early treatment with lasmiditan for 7 consecutive days from day 1 after surgery delayed the onset of mechanical allodynia in SNI rats. A study has indicated that the half-life of ZLN005 is 11.46 ± 0.67 min in rats ( Sun et al, 2018 ). A clinical study indicated that plasma concentrations of lasmiditan peaked at 1.5–2 h post dose, with a terminal half-life of approximately 4 h ( Tsai et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although activation of PGC-1α can occur through the β-adrenergic receptor (β-AR)/3'-5'-cyclic adenosine monophosphate (cAMP) and AMP-activated protein kinase (AMPK) pathways [33,34], more recent studies have utilized a small, benzimidazole compound ZLN005 to induce PGC-1α expression [35][36][37][38][39][40][41]. Hence, the application of ZLN005 to activate PGC-1α might be an effective approach to promote cardiomyocyte maturation.…”
Section: Agingmentioning
confidence: 99%
“…However, this modality is unlikely to soon become widely applicable due to the need for myeloablative conditioning, prolonged and intense follow-up, and off-target potential and cost, which is likely to be between $1 and $2 million for a onetime dose. [42][43][44][45][46] A small molecule like ZLN005, with oral bioavailability 25,47 and effects additive to HU and possibly other HbF inducers, might have more therapeutic potential where SCD is most prevalent.…”
Section: Discussionmentioning
confidence: 99%